2002
DOI: 10.1038/sj.hdy.6800010
|View full text |Cite
|
Sign up to set email alerts
|

Nested clade analysis and the genetic evidence for population expansion in the phylogeography of the golden-striped salamander, Chioglossa lusitanica (Amphibia: Urodela)

Abstract: The golden-striped salamander, Chioglossa lusitanica, is a streamside species distributed in the northwest of the Iberian Peninsula. We gathered cytochrome b mitochondrial DNA sequence data from samples across the species range and used nested clade distance analysis to assess evolutionary processes explaining the geographical distribution of mtDNA diversity in Chioglossa lusitanica. A significant association was observed between genetic structure and geography. The geographical patterns were explained by past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 30 publications
7
89
1
3
Order By: Relevance
“…Templeton's (2004) latest inference key was used to infer processes involved in any statistically significant associations observed. It has recently been suggested that some NCA inferences may be flawed, and should therefore be supported by the use of alternative analytical techniques (eg Alexandrino et al, 2002;Masta et al, 2003;Templeton, 2004). We therefore applied the coalescent/maximum-likelihood approach implemented in FLUCTUATE ver.…”
Section: Discussionmentioning
confidence: 99%
“…Templeton's (2004) latest inference key was used to infer processes involved in any statistically significant associations observed. It has recently been suggested that some NCA inferences may be flawed, and should therefore be supported by the use of alternative analytical techniques (eg Alexandrino et al, 2002;Masta et al, 2003;Templeton, 2004). We therefore applied the coalescent/maximum-likelihood approach implemented in FLUCTUATE ver.…”
Section: Discussionmentioning
confidence: 99%
“…This included a data set of 12S-tRNA Val -16S sequence for 32 ingroup taxa and 5 outgroups (Caccone et al, 1994;Steinfartz et al, 2002;Titus and Larson, 1995;Zajc and Arntzen, 1999) and a data set of Cytochrome b sequences for 32 ingroup taxa and 2 outgroups (Alexandrino et al, 2002;Caccone et al, 1994;Chan et al, 2001;Chippindale et al, 2001;García-París et al, 2003;Hedges et al, 1992;Tan and Wake, 1995). Sequences in the 12S-tRNA Val -16S region range from approximately 300-1000 bp in length.…”
Section: Taxon Sampling and Data Collectionmentioning
confidence: 99%
“…Analysing a fragment of only 329 bp in 17 populations of the goldenstriped salamander Chioglossa lusitanica, Alexandrino et al (2000) found 1-4 haplotypes per population (mean 1.76), with a sequence divergence between haplotypes of up to 3.2% and an overall nucleotide diversity of 1.4%. A subsequent study in which 700 bp was sequenced in 124 individuals from 17 localities identified 30 haplotypes with sequence divergence ranging from 0.14 to 2.14% and an overall nucleotide diversity of 0.99% (Alexandrino et al, 2002). They found that 10 out of 12 localities with samples of n > 5 were polymorphic with 2-5 haplotypes differing by 1-5 mutations.…”
Section: Differentiation Within the M Madagascariensis Groupmentioning
confidence: 99%